2018
DOI: 10.1007/s00264-018-3770-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival, complications and functional outcomes of cemented megaprostheses for high-grade osteosarcoma around the knee

Abstract: With effective management strategies for complications, cemented endoprosthetic reconstruction of the proximal tibia and distal femur using an extensor mechanism reconstruction technique provides a reliable method of reconstruction following tumour resection around the knee. Level of Evidence Level IV, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
0
51
0
1
Order By: Relevance
“…Our own series of 520 non metastatic osteosarcomas treated with limb salvage surgery (excluding ECRT) had a similar local recurrence rate of 10% . In the series by Mavrogenis et al 8% (12 of 151) of osteosarcomas reconstructed with a megaprosthesis had local recurrence while Zhang et al documented 9% (10 of 108) local recurrence in their study of megaprostheses for high‐grade osteosarcoma around the knee. Similarly, the series by Ortiz‐Cruz et al demonstrated a 9% (four of 47) rate of local recurrence in high grade sarcomas reconstructed with an intercalary allograft.…”
Section: Discussionmentioning
confidence: 51%
“…Our own series of 520 non metastatic osteosarcomas treated with limb salvage surgery (excluding ECRT) had a similar local recurrence rate of 10% . In the series by Mavrogenis et al 8% (12 of 151) of osteosarcomas reconstructed with a megaprosthesis had local recurrence while Zhang et al documented 9% (10 of 108) local recurrence in their study of megaprostheses for high‐grade osteosarcoma around the knee. Similarly, the series by Ortiz‐Cruz et al demonstrated a 9% (four of 47) rate of local recurrence in high grade sarcomas reconstructed with an intercalary allograft.…”
Section: Discussionmentioning
confidence: 51%
“…Although the five-year survival rate has been improved to 60-75% thanks to the rapid development of treatment strategies, the prognosis remained poor for the complicated carcinogenesis of OS is still unclear [2]. erefore, it is of great urgency to seek for new biomarkers that targeted preventive and/or therapeutic interventions for OS patients to improve the clinical outcome [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D-printed prosthesis for the patients in our study were designed by ourselves. According to previous research, aseptic loosening would be the most common complication for the patients with prosthesis replacement in distal femur [16][17]. So, the proximal femoral medullary stalk of the prosthesis and the lateral auxiliary plate would be biological xation type by 3D-printed technology to promote the bone union and prevent the prosthesis from loosening and rotation.…”
Section: Discussionmentioning
confidence: 99%